2021
DOI: 10.1016/j.rbms.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the government public economic benefits attributed to investing in assisted reproductive technology: a South African case study

Abstract: Limited resources and high treatment costs are arguments often used in many public health systems in low-and middleincome countries to justify providing limited treatments for people with infertility. In this analysis, we apply a government public economic perspective to evaluate public subsidy for in-vitro fertilization (IVF) in South Africa. A fiscal model was developed that considered lifetime direct and indirect taxes paid and government transfers received by a child conceived by IVF. The model was constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…However, infertility is itself a widely prevalent cause of significant health burden for millions of people ( Makuch et al , 2010 ; Mascarenhas et al , 2012 ; Cox et al , 2022 ) that should be the addressed alongside other health needs to achieve universal health coverage ( Starrs et al , 2018 ). The results of this review add to the calls for governments in LMICs to increase investments in the provision of fertility treatment, by better integrating infertility in the national health policy and financing ( WHO, 2020 ; Connolly et al , 2021 ). Yet, in comparison with HICs, this review demonstrates that there are limited data on costs of ART from LMICs to inform policies and financing.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, infertility is itself a widely prevalent cause of significant health burden for millions of people ( Makuch et al , 2010 ; Mascarenhas et al , 2012 ; Cox et al , 2022 ) that should be the addressed alongside other health needs to achieve universal health coverage ( Starrs et al , 2018 ). The results of this review add to the calls for governments in LMICs to increase investments in the provision of fertility treatment, by better integrating infertility in the national health policy and financing ( WHO, 2020 ; Connolly et al , 2021 ). Yet, in comparison with HICs, this review demonstrates that there are limited data on costs of ART from LMICs to inform policies and financing.…”
Section: Discussionmentioning
confidence: 91%
“…ART financing by the governments in LMICs depends mainly on the cost–benefit value perceived by the state, given the relatively high ART costs ( Darvishi et al , 2020 ). In this regard, financing ART may represent a good governmental investment by enhancing immediate reproductive health while also generating positive financial returns in future tax contributions, including in LMICs ( Connolly et al , 2021 ). Further opportunities to mitigate costs of treatment in low resource settings could include the implementation of low-cost options for ART ( Chiware et al , 2021 ); however, low cost should not lead to a compromise on quality ( Aleyamma et al , 2011 ; Arakkal et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In low- and middle-income countries, limited ART treatments are provided for infertile people because of limited resources and high treatment costs. However, a South African case study estimating the government public economic benefits attributed to investing in ART suggested that funding for IVF may create positive economic benefits and promote the sustainability of health systems [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the policy-making space, differential power existed; United Nations agencies for example play an important role on both SRH and UHC issues, depending on their international norms and guidelines. Priority-setting process theoretically allows a diverse range of healthcare stakeholders to articulate their preferred values and agendas in order to achieve consensus on the direction for a country's health agenda [23]. However, based on the interviews it was noted that the key SRH partners expressed divers contributions in the process of infertility care services prioritization and its inclusion within the Health Benefit Package (HBP).…”
Section: "……A Memorandum Has Been Sent In the Form Of A Claim Book To...mentioning
confidence: 99%